2004
DOI: 10.1292/jvms.66.77
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Granular Cell Tumor in a Dog

Abstract: ABSTRACT. A 12-year-old female miniature poodle showed a 3-month history of neurological signs. Magnetic resonance imaging disclosed a high intensity tumor mass in the right cerebral hemisphere with compression of the lateral ventricle. At necropsy, a 2 × 3 cm white, friable mass was found in the right ventral pyriform lobe. Microscopically, the tumor cells were large, polygonal to round cells supported by a sparse fibrovascular stroma. The tumor cells typically possesed finely granular, pale eosinophilic cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 15 publications
2
27
2
Order By: Relevance
“…1 Canine cerebral GCTs appeared to be of meningeal cell origin 2 or mesenchymal and neural nature. 3 The tumor under study appeared to develop outside the neural parenchyma and histologic examination showed features commonly observed in meningeal tumors, such as psammoma body-like patterns and areas of cholesterol degeneration. Based on the negative staining for GFAP expression, the tumor was not considered to be of astrocytic derivation.…”
mentioning
confidence: 88%
“…1 Canine cerebral GCTs appeared to be of meningeal cell origin 2 or mesenchymal and neural nature. 3 The tumor under study appeared to develop outside the neural parenchyma and histologic examination showed features commonly observed in meningeal tumors, such as psammoma body-like patterns and areas of cholesterol degeneration. Based on the negative staining for GFAP expression, the tumor was not considered to be of astrocytic derivation.…”
mentioning
confidence: 88%
“…97 Granular cell meningioma has been considered an uncommon variant of meningioma but is probably a completely unrelated tumor. Its staining properties are variable in dogs 43,70 and a cat. 78 Granular cell tumors are also occasionally found intra-axially.…”
Section: Meningiomasmentioning
confidence: 99%
“…In fact, GCT is the most common intracranial tumor in rats. 35 However, fewer than a dozen reports of GCTs in the CNS of dogs exist in the literature, 3,[13][14][15]19,26 and there is only 1 report of GCTs in the peripheral nervous system of dogs. 18 The histogenesis remains disputed.…”
mentioning
confidence: 99%